Paths of cucumber green mottle mosaic virus disease spread and disinfectant‐based management. (17th August 2020) - Darzi, Elinor; Lachman, Oded; Smith, Elisheva; Koren, Amnon; Klein, Eyal; Pass, Nadav; Frenkel, Omer; Dombrovsky, Aviv
Abstract: Cucumber green mottle mosaic virus (CGMMV) assigned to the genus Tobamovirus is considered a major disease cause of cucurbits worldwide. A primary route for CGMMV disease spread is via mechanical contact. The virus is highly stable and adheres to various agricultural equipment. In the current study, we examined means to inactivate the virus and reduce disease spread via planting equipment and supplies using various chemicals. We have found that incubations of CGMMV‐infected cucumber plant extracts with MENNO‐Florades 2%, Virocid 3% or Green Up D 20% inactivated the virus and prevented disease spread in a biological assay. Stabilised chlorine formulation (KlorBac), which has the active ingredient troclosene‐sodium (sodium dichloroisocyanurate, SDIC) at 2, 000 ppm, was efficient in disinfecting CGMMV‐contaminated grafting knives in 2 s. Similarly, immersing virus contaminated grafting knives for 2 s in 20% (wt/vol) non‐fat milk powder reduced infectivity of the contaminated knives. CGMMV‐contaminated nursery sowing trays could constitute a primary infectious viral source transmitted via irrigation water. CGMMV‐contaminated sowing trays immersed in KlorBac 2, 000 ppm or active oxygen (Huwa‐San TR‐50) 1%, were efficiently disinfected. Interestingly, hydrophobic insulation of the CGMMV‐contaminated trays using dry silicone layers reduced initiation of the viral primary infection in CGMMV‐contaminated new sowing trays but was less efficient in CGMMV‐contaminated re‐used trays. Importantly, Septadine (0.5% chlorhexidine gluconate) was not effective in disinfection of grafting knives. Notably, CGMMV‐infected cucumber plant extract incubated with 20% (wt/vol) non‐fat milk powder was refractory to the milk suggesting that virus release from surfaces did not necessarily involve virus inactivation. Abstract : Cucumber green mottle mosaic virus (CGMMV) assigned to the genus Tobamovirus is considered a major disease cause of cucurbits worldwide. In order to achieve maximum disinfection of CGMMV we strongly recommend establishing high standard hygienic conduct at the nursery various surfaces using MENNO‐Florades 2% solution, active oxygen (Huwa‐San) 1% solution and KlorBac 2, 000 ppm; these chemicals could be useful as disinfectants of sowing trays as well. Interestingly, coating contaminated new trays with silicone is a promising strategy for tray disinfection. Agricultural tools, for example, grafting knives could be disinfected using 20% skim milk or KlorBac 2, 000 ppm solutions before and during the grafting procedure.